Pengembangan Application Programing Interface untuk Pemesanan Online Usaha Mikro, Kecil dan Menengah Berdasarkan Radius Tertentu Menggunakan Metode Haversine Formula dan Metode Agile - Dawam Agung Pribadi; Sudarno Sudarno; Murni Handayani (Teknik Informatika Universitas Pamulang, 2022)
March 2020 was the beginning of the pandemic period in Indonesia, this had an impact on many business sectors, one of which was micro, small and medium enterprises (MSMEs). This pandemic period has forced the government to limit direct interaction activities. So it takes a media transaction in order to reduce public activity in direct transactions. The design method uses the Agile SDLC which is suitable for rapid adaptation in building short-term systems. To ensure the system runs as desired, Black Box Testing and White Box Testing are carried out. The presence of an API (Application Programing Interface) with the calculation of the radius of the Haversine Formula method can detect the distance of the nearest MSME up to a radius of 1 Km. Based on research conducted using 20 samples that were tested, it resulted in an average distance difference of 0.004 from the distance of Maps. So that customers can easily find MSMEs around them and make transactions or orders online.